Enriching papaya’s value-added through community-oriented food processing training - Reni Untarti; Agung Nugroho; Cicih Wiarsih (University of Merdeka Malang, 2026)
Papaya represents one of the most abundant agricultural commodities in Dukuh Ceger, Linggasari Village, Banyumas Regency. However, its utilization remains limited to direct consumption, resulting in relatively low commercial value, particularly during harvest seasons. This community service program aimed to improve local communities by enhancing their capacity to process papaya into value-added food products. The program adopted a participatory approach through training, hands-on practice, mentoring, and evaluation. A total of 35 participated in the training, which focused on producing papaya candy, papaya chips, and papaya pudding. Pre-test and post-test assessments was conducted for evaluation, demonstrating a significant increase in participants’ understanding across several aspects, including processing techniques, product diversification, and commercial value. The results demonstrated various improvements, particularly 31 percent increase in product knowledge, 66 percent increase in understanding commercial value, 51 percent increase in processing skills, and 63 percent increase in perceived community benefits. In addition, 86 percent of participants actively engaged during the activities, and the average satisfaction score reached 4.64 on a 5-point scale. These findings demonstrate that the program effectively improved participants’ knowledge and practical skills, while also increasing awareness of papaya’s commercial value potential. The program contributes to strengthening community capacity and opens opportunities for developing sustainable, locally based business initiatives.